Component of sawt in hadeeth texts: Musiqi al-Quran in the art of tarannum - Wan Hilmi Wan Abdullah; Wan Fakhrul Razi Wan Mohamad; Ahmad Shafiq Mat Razali; Farah Ilyani Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2022)
The art of the reciting of the Quran is the concept of the musiqi al-Quran or the melody of the Quran in the Quranic reciting. It is associated with vocal artistry composing of two fundamental elements: tone and rhythm. The tarannum style of Quranic recitation is executed with vocal artistry that is simple, natural, and without the complement of any musical instrument; yet, the melodious recitation captivates and mesmerizes the listener. The objective of this qualitative study is to examine the vocal (sawt) elements of tarannum, using texts found in Hadeeth literature as a basis of the analysis. Data was collected through the analysis of documents, while data analysis was performed through the use of the ATLAS ti 8.0 software. The study finds that in the texts of the Hadeeth, a total of sixteen components of sawt al-Quran have been discussed: tarji’; qiraah layyinah’; husn al-sawt; ghaddan; husn al-tarannum; jahr; tazyin; husn al-Quran; husn al-qira’ah; huzn; tabaki; taghanni bi al-Quran; mizmar; tahsin; tahbir and talahun. The analysis in this study further leads to an implication that the absence of the aforementioned elements, affect a reader’s ability for tadabbur (contemplation) and khushu’ (concentration) in their Quranic recitation.